Impact of Online Learning on Stress and Fatigue Using GSR and SOFI Measurements - Kristianti, Meilena; Sarvia, Elty (School of Industrial and System Engineering, Telkom University, 2024)
The early days of university are often a period of great change and stress for freshman students. Freshman and sophomore students in the Industrial Engineering bachelor’s degree program at University X are adapting to a more flexible learning environment, running two different learning methods, namely synchronous and asynchronous learning methods. This study was conducted to analyze the classification of stress and fatigue levels of undergraduates in the Bachelor Program in Industrial Engineering at University X. Industrial Engineering bachelor’s degree program of University X when undergoing lectures. Stress levels were measured objectively using Galvanic Skin Response (GSR) with a gel electrode type. In contrast, fatigue levels were assessed subjectively through the Swedish Occupational Fatigue Inventory (SOFI) questionnaire. The analysis revealed that the stress levels of students during learning, whether through synchronous or asynchronous methods, were categorized as high, with a higher mean value observed in the synchronous learning method. Conversely, fatigue was classified as mild. Based on these findings, this study proposes implementing structured break schedules during synchronous learning sessions and optimizing asynchronous methods by integrating interactive yet less demanding activities to reduce stress and improve student well-being. Additionally, further ergonomic adjustments to the learning setup and duration are recommended to minimize fatigue.